Expansion of human mesenchymal stem cells in a fixed-bed bioreactor system based on non-porous glass carrier – Part A: Inoculation, cultivation, and cell harvest procedures - Weber, Christian; Freimark, Denise; Portner, Ralf; Pino-Grace, Pablo; Pohl, Sebastian; Wallrapp, Christine; Geigle, Peter; Czermak, Peter (My University, 2018)
Human mesenchymal stem cells (hMSC) are a promising cell source for several applications of regenerative medicine. The used cells are either autologous or allogenic, whereas the latter enables, especially by using of stem cell lines, a production of cell therapeutic or tissue engineered implants in stock. Therefore, the usually small initial cell number has to be increased. For that purpose bioreactors are demanded, which offer the controlled expansion of the hMSC under GMP-conform conditions. In this study, divided in part A and B, a fixed bed bioreactor system based on non-porous borosilicate glass spheres for the expansion of hMSC, demonstrated with the model cell line hMSC-TERT, is introduced. The system offers a comfortable automation of the inoculation, cultivation, and harvesting procedures. Furthermore the bioreactor owns a simple design which benefits the manufacturing as disposable. Part A is focused on the inoculation, cultivation, and harvesting procedures. Cultivations were performed in lab scales up to a bed volume of 300 cm3. It could be shown that the fixed bed system, based on 2-mm borosilicate glass spheres, as well as the inoculation, cultivation, and harvesting procedures are suitable for the expansion of hMSC with high yield and vitality.
Keywords: Mesenchymal stem cells; hMSC-TERT; Fixed-bed reactor; Glass carrier